Saúde sexual e reprodutiva uma intervenção dialógica - Lima Neto, José Luiz de [UNESP]; Oliveira, Rodrigo Cena de [UNESP]; Duarte, Marli Teresinha Cassamassimo [UNESP]; Alencar, Rúbia Aguiar [UNESP]; Almeida, Margareth Aparecida Santini de [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Introduction: The project proposes to carry out the confrontation of sexually transmitted diseases (STDs) / AIDS and unwanted pregnancies through community interventions that support informed and safe decisions in the field of sexual and reproductive health, especially of vulnerable groups such as young people and teens. Objectives: To promote continuing education on sexual and reproductive education through the organization of a multidisciplinary group composed of university students for study and continuing education on sexual health , family planning, STD / Aids and reproductive and STD / AIDS and develop health education activities among adolescents elementary school . . Methods The project is developed in partnership between the Faculty of Medicine of Botucatu / UNESP and the state Department of Education, with students (9th grade) from two secondary schools in the city of Botucatu (SP), in Brazil. The activities in schools are based on group dynamics and dialogical education, guided by the contents proposal of the Health and Prevention Program in schools, such as: body, sexually transmitted diseases, teen pregnancy, vulnerability, etc. After each activity an evaluation form is distributed among students and a suggestion box is passed around for issues or questions to be discussed in subsequent meetings. The pre-graduates' perception of performed activities is garnered (concerning easiness, difficulties, and suggestions). Results University extension, while adding to the completeness of pre-graduate training, contributes through educational actions in health and STDs / AIDS prevention, to the free and informed decision-making and promotion of sexual and reproductive rights among secondary school students. Keywords: STD / AIDS, young, university extension, education experience.

Introdução: O projeto se propõe a realizar o enfrentamento de doenças sexualmente transmissíveis (DST)/aids e gravidez indesejada por meio de intervenções comunitárias que subsidiem decisões informadas e seguras no campo da saúde sexual e reprodutiva, especialmente, de grupos vulneráveis, como jovens e adolescentes. Objetivos: Promover a formação continuada em educação sexual e reprodutiva por meio da organização de um grupo multidisciplinar, integrado por alunos da graduação, para estudo e formação continuada sobre saúde sexual, planejamento familiar, DST/Aidas e reprodutiva e prevenção de DST/aids e desenvolver ações de educação em saúde entre adolescentes do ensino fundamental. Métodos O projeto é desenvolvido em parceria entre a Faculdade de Medicina de Botucatu/UNESP e a Secretaria Estadual de Educação, junto a alunos (9 º ano) de duas escolas de ensino fundamental do município de Botucatu/SP/Brasil. As atividades nas escolas se dão mediante dinâmica de grupo, baseada na educação dialógica, pautadas em conteúdos propostos pelo Programa Saúde e Prevenção nas escolas, como: corpo, doenças sexualmente transmissíveis, gravidez adolescente, vulnerabilidade, etc. Após cada atividade é distribuída uma ficha de avaliação entre os alunos e uma caixa para sugestão de temas ou dúvidas a serem desenvolvidas nos próximos encontros. Entre os graduandos é levantada a percepção dos mesmos a respeito da atividade desenvolvida (facilidades, dificuldades e sugestões). Resultados a extensão universitária tem favorecido a complementação da formação dos graduandos, assim como, proporcionando ações de educação em saúde e prevenção em DST/aids, contribuindo com a possibilidade de escolhas livres e informadas e promoção dos direitos sexuais e reprodutivos de jovens e adolescentes do ensino fundamental.
Keywords: Sexual and reproductive health; Prevention; Sexually transmitted diseases and AIDS; Saúde sexual e reprodutiva; Prevenção; Doenças sexualmente transmissíveis e aids